Characterization of Oily and Non-Oily Natural Sediments in Palm Oil Mill Effluent - Alrawi, Reem A.; Nik Ab Rahman, Nik Norulaini; Ahmad, Anees; Ismail, Norli; A. K., Mohd Omar (Hindawi Publishing Corporation, 2013)
Palm oil is one of the many vegetable oils widely consumed around the world. e production of palm oil requires voluminous amount of water with the concurrent generation of large amount of wastewater known as palm oil mill effluent (POME). POME is a mixture of water, oil, and natural sediments (solid particles and